Determinants of Postnatal Care Service Utilization in Indonesia: A Secondary Analysis Using the Indonesian Health and Demographics Survey - Idris, Haerawati; Syafriyanti, Willyana (Makara Journal of Health Research, 2021)
Background: The postnatal complication that occurs in the first week after childbirth is one of the causes of maternal death in Indonesia. However, it can be prevented with postnatal care (PNC). This study aims to analyze the determinants of PNC service utilization in Indonesia. Methods: This quantitative study employed a cross-sectional study design and used secondary data from the Indonesian Health and Demographics Survey of 2017. The sample consisted of 14,724 women aged 15–49 years. We assessed the predictors of PNC service utilization using multivariate logistic regression models. Results: About 78.4% of the respondents utilized PNC services. The factors that have a significant association with PNC service utilization include the following: college and secondary of level education, working status, high economic status, residence in the Java–Bali region, delivery assistance by a health worker, delivery by cesarean section, and complete antenatal care during pregnancy. Among these, residence in the Java–Bali region is the most dominant factor associated with PNC service utilization in Indonesia. Conclusions: The difference area is a key factor in PNC service utilization. Government efforts to improve PNC service utilization must consider the equitable distribution of health facilities and health workers throughout the country.